2018
DOI: 10.1111/jvim.15142
|View full text |Cite
|
Sign up to set email alerts
|

Pathological classification of equine recurrent laryngeal neuropathy

Abstract: Recurrent Laryngeal Neuropathy (RLN) is a highly prevalent and predominantly left‐sided, degenerative disorder of the recurrent laryngeal nerves (RLn) of tall horses, that causes inspiratory stridor at exercise because of intrinsic laryngeal muscle paresis. The associated laryngeal dysfunction and exercise intolerance in athletic horses commonly leads to surgical intervention, retirement or euthanasia with associated financial and welfare implications. Despite speculation, there is a lack of consensus and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 124 publications
(415 reference statements)
0
31
0
Order By: Relevance
“…Our data were derived from a large sample size, ensuring the results were free from bias (blinding), and, by using a continuous scale for RLN severity to phenotype individuals, misclassification of disease status was avoided: When using laryngoscopy to phenotype horses for RLN, daily variations in applied grades can cause horses to be classified incorrectly as control, subclinical, or clinical cases . Further, the extensive fiber type grouping that occurs in intrinsic laryngeal muscles supplied by diseased RLns in affected horses very likely means that clinical phenotyping (eg, when using resting or exercising laryngoscopy) is inaccurate …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our data were derived from a large sample size, ensuring the results were free from bias (blinding), and, by using a continuous scale for RLN severity to phenotype individuals, misclassification of disease status was avoided: When using laryngoscopy to phenotype horses for RLN, daily variations in applied grades can cause horses to be classified incorrectly as control, subclinical, or clinical cases . Further, the extensive fiber type grouping that occurs in intrinsic laryngeal muscles supplied by diseased RLns in affected horses very likely means that clinical phenotyping (eg, when using resting or exercising laryngoscopy) is inaccurate …”
Section: Discussionmentioning
confidence: 99%
“…RLN can now be classified as a distal axonopathy, without an associated degeneration of the cell bodies of the RLns . The advantage of a more specific classification is that it focuses the list of likely etiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also confirmed that the K40 horse SOD1 variant was present in an equine ancestor, 4-4.5 million years ago by blasting the SOD1 exon 2 sequence of the modern horse genome to the ancient horse genome, 9 and it appears that evolutionary pressures have not resulted in the removal of this residue; to the best of the authors' knowledge there is no publically available horse genomes where a different residue can be found at the 40 th codon, and within our laboratory we have identified this residue at the 40 th codon in over seven different horse breeds (Supplementary Figure 1). 11 An important pathological feature of ALS-models is higher cellular ROS levels in cells expressing mutant SOD1 variants. Indeed in dogs, to develop the DM phenotype, advancing age as well as the expression of the K40 SOD1 protein is typically needed, 3 highlighting that the K40 residue might only be pathogenic under certain circumstances.…”
Section: F I G U R E 4 a Sod1 Immunocytochemistry Of Control And Virmentioning
confidence: 99%